The Effect of Combined Aerobic and Resistance Exercise on Biochemical Factors in Patients with Type 2 Diabetes Mellitus - Soulmaz Rahbar; Sedigheh Sadat Naimi (Vesnu Publications, 2019)
Introduction: Diabetes mellitus is a common health problem worldwide, especially in Asia. Exercise training plays an important role in controlling diabetes variables. The aim of this research was to consider the effectiveness of exercise on biochemical parameters in patients with type 2 diabetes mellitus. Materials and Methods: This randomized controlled clinical trial study was carried out with 40 patients with type 2 diabetes mellitus selected out of 702 volunteers. These individuals were randomly divided to two groups, combined (aerobic and resistance) exercise and control. Intervention protocol included 24 sessions (8 weeks) of aerobic exercise on the treadmill with zero slope, three days per week for 30 minutes per session. Intensity of training protocol was 50-70 percent of maximum heart rate, and that subjects wear a weighted vest. Measurements of parameters were done before and after 24 sessions. Results: Basically, there were no significant differences in variable values. After eight weeks, fasting blood sugar (FBS) (P = 0.059), glycosylated hemoglobin (HbA1c) (P = 0.333) were significantly reduced in the combined group; but not low-density lipoprotein (LDL), very low-density of lipoprotein (VLDL), high-density lipoprotein (HDL), total cholesterol, triglyceride, and high-sensitivity C-reactive protein (HS-CRP) (P > 0.050 for all). Alternatively, the value remained unchanged in the combined group while it was increased in the control group (P = 0.001). Conclusion: 24 sessions of aerobic exercise improved FBS and HbA1c in patients with type 2 diabetes mellitus. However, longer training duration is deemed to need to modify other variables.